Control of the Single‐Molecule Magnet Behavior of Lanthanide‐Diarylethene Photochromic Assemblies by Irradiation with Light. Issue 39 (11th August 2014) - Pinkowicz, Dawid; Ren, Min; Zheng, Li‐Min; Sato, Saki; Hasegawa, Miki; Morimoto, Masakazu; Irie, Masahiro; Breedlove, Brian K.; Cosquer, Goulven; Katoh, Keiichi; Yamashita, Masahiro
Abstract Lanthanide‐based extended coordination frameworks showing photocontrolled single‐molecule magnet (SMM) behavior were prepared by combining highly anisotropic DyIII and HoIII ions with the carboxylato‐functionalized photochromic molecule 1, 2‐bis(5‐carboxyl‐2‐methyl‐3‐thienyl)perfluorocyclopentene (H2dae), which acts as a bridging ligand. As a result, two new compounds of the general formula [LnIII2(dae)3(DMSO)3(MeOH)⋅10 MeOH]n (M=Dy for 1 a and Ho for 2) and two additional pseudo‐polymorphs [DyIII2(dae)3(DMSO)3(H2O)⋅x MeOH]n (1 b) and [DyIII2(dae)3(DMSO)3(DMSO)⋅x MeOH]n (1 c) were obtained. All four compounds have 2D coordination‐layer topologies, in which carboxylate‐bridged Ln2 units are linked together by dae2− anions into grid‐like frameworks. All four compounds exhibited a strong reversible photochromic response to UV/Vis light. Moreover, both 1 a and 2 show field‐induced SMM behavior. The slow magnetic relaxation of 1 a is influenced by the photoisomerization reaction leading to the observation of the cross‐effect: photocontrolled SMM behavior.